2015
DOI: 10.4236/jdm.2015.52007
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Glyburide Compared to Insulin in the Management of Gestational Diabetes Mellitus: A Systematic Review

Abstract: Background: Insulin therapy has been the mainstay in managing women with gestational diabetes mellitus (GDM), but some disadvantages of insulin have led to the use of glyburide, which is inexpensive in some countries, to manage GDM. However, there has been debate over its effectiveness, efficacy and safety when compared to insulin for maternal glycaemic control, and some adverse neonatal outcomes in GDM. Method: A systematic review of eight randomised controlled trial (RCT) studies was undertaken to compare gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
2
1
1
Order By: Relevance
“…Since the management of GDM is primarily aimed at the glycemic target to reduce the incidence of fetal and maternal complications 8,36 , metformin and glibenclamide can be used as safe alternatives to insulin. This is supported by the fact that there was no significant difference in the blood glucose levels between all the treated groups at the end of this research and it corroborates with the previous reports from the review of randomized controlled trials which showed that there was no significant difference in maternal fasting glucose between glyburide (glibenclamide) and insulin although there was slightly lower fasting blood glucose in the insulin group than in glyburide group 37 , and between OHAs and insulin 8 . It was even showed that maternal complications were higher in insulin-treated GDM women compared to metformin and glibenclamide 8 .…”
Section: Maternal Blood Glucose and Body Weightsupporting
confidence: 91%
See 1 more Smart Citation
“…Since the management of GDM is primarily aimed at the glycemic target to reduce the incidence of fetal and maternal complications 8,36 , metformin and glibenclamide can be used as safe alternatives to insulin. This is supported by the fact that there was no significant difference in the blood glucose levels between all the treated groups at the end of this research and it corroborates with the previous reports from the review of randomized controlled trials which showed that there was no significant difference in maternal fasting glucose between glyburide (glibenclamide) and insulin although there was slightly lower fasting blood glucose in the insulin group than in glyburide group 37 , and between OHAs and insulin 8 . It was even showed that maternal complications were higher in insulin-treated GDM women compared to metformin and glibenclamide 8 .…”
Section: Maternal Blood Glucose and Body Weightsupporting
confidence: 91%
“…The results of this research show that metformin and glibenclamide are safe alternatives to insulin in GDM at the doses used. Although head-to-head comparison of insulin and OHA use in pregnancy is still scanty in animal research, there are reviews, meta-analyses and randomized clinical trials 37,8,71,72,73,74 whose authors reported metformin and glibenclamide as being safe and effective alternatives to insulin in the treatment of GDM with minimal or no complications in both the fetus and mothers. Direct comparison of metformin and glibenclamide showed higher glycemic control by metformin than glibenclamide 75,57 .…”
Section: Fetal Pancreasmentioning
confidence: 99%
“…This failure rate of glyburide can be explained by the range of failure rate of glyburide in studies comparing glyburide and insulin worldwide; which is 2.43 to 20.83% (average 6.64%). 24 Three Indian studies which have compared glyburide with insulin shows failure rate ranging from 0 to 6.25% (average 2.8%) and this is comparable with our study findings.…”
supporting
confidence: 82%
“…This meta-analysis included eight randomized trials comparing glyburide and insulin in the management of gestational diabetes mellitus. 24 Failure rate of glyburide in our study is quite low compared to the studies which have compared metformin and glyburide. This may be because of treating mild level of hyperglycemia when diagnosing GDM according to single 75 g 2 hr OGTT value.…”
contrasting
confidence: 41%